1999
DOI: 10.1073/pnas.96.18.10170
|View full text |Cite
|
Sign up to set email alerts
|

Role for yeast inhibitor of apoptosis (IAP)-like proteins in cell division

Abstract: Inhibitors of apoptosis (IAPs) are a family of proteins that bear baculoviral IAP repeats (BIRs) and regulate apoptosis in vertebrates and Drosophila melanogaster. The yeasts Saccharomyces cerevisiae and Schizosaccharomyces pombe both encode a single IAP, designated BIR1 and bir1, respectively, each of which bears two BIRs. In rich medium, BIR1 mutant S. cerevisiae underwent normal vegetative growth and mitosis. Under starvation conditions, however, BIR1 mutant diploids formed spores inefficiently, instead und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(139 citation statements)
references
References 34 publications
6
133
0
Order By: Relevance
“…Even a 2-h treatment of transformed 423DiR-1 cells with LY294002 and/or U0126 markedly diminished the localization of survivin to the mitotic spindle apparatus (data not shown). This suggests that, apart from direct or indirect transcriptional activation of survivin by c-H-Ras, other Ras-mediated effects on downstream targets are required to render survivin functional in its ancient role as protector of genome integrity (Li et al, 1998;Fraser et al, 1999;Uren et al, 1999Uren et al, , 2000. In this context, it appears interesting that the Raf/MEK/MAPK pathway is necessary also for the G2/M progression, where 40% of MAPKs was found associated with microtubuli (Hayne et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even a 2-h treatment of transformed 423DiR-1 cells with LY294002 and/or U0126 markedly diminished the localization of survivin to the mitotic spindle apparatus (data not shown). This suggests that, apart from direct or indirect transcriptional activation of survivin by c-H-Ras, other Ras-mediated effects on downstream targets are required to render survivin functional in its ancient role as protector of genome integrity (Li et al, 1998;Fraser et al, 1999;Uren et al, 1999Uren et al, , 2000. In this context, it appears interesting that the Raf/MEK/MAPK pathway is necessary also for the G2/M progression, where 40% of MAPKs was found associated with microtubuli (Hayne et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of survivin to cell division is evolutionary conserved. In yeast and C. elegans, proper chromosomal separation is strictly dependent on the action of proteins with survivin-like BIR domains (Uren et al, 1999;Fraser et al, 1999). These proteins in lower organisms, however, lack antiapoptotic activity, indicating that the survival function of the BIR-only containing proteins was superimposed by evolution.…”
Section: Introductionmentioning
confidence: 99%
“…This cytokinesis defect could be partially suppressed by transgenic expression of survivin. In the yeast S. cerevisiae and S. probe there is only a single IAP protein, Bir1, which contains two BIRs [31]. This gene is required for spindle elongation and efficient meiotic division [31], indicating the cell cycle regulation function of IAP family proteins is evolutionarily conserved.…”
Section: Iaps and Cell Cycle Controlmentioning
confidence: 99%
“…In the yeast S. cerevisiae and S. probe there is only a single IAP protein, Bir1, which contains two BIRs [31]. This gene is required for spindle elongation and efficient meiotic division [31], indicating the cell cycle regulation function of IAP family proteins is evolutionarily conserved. It is not clear at present whether the cell-cycle regulating activity of these BIR-containing proteins is related to their anti-apoptotic function.…”
Section: Iaps and Cell Cycle Controlmentioning
confidence: 99%
“…The present study indicated that BIRC2/CIAP1 induced changes in the apoptosis process. This gene belongs to a family of highly conserved anti-apoptotic proteins first identified in baculovirus and later in eukaryotic species from yeast to mammals (39,40). It has been reported that BIRC2/CIAP1 is an inhibitor of apoptosis and overexpressed through 11q22 amplification in cell lines derived from esophageal squamous cell carcinomas (41).…”
Section: Cgy --------------------------------------------------------mentioning
confidence: 99%